2015
DOI: 10.11648/j.ajls.s.2015030601.22
|View full text |Cite
|
Sign up to set email alerts
|

Stock Status of Pufferfish <i>Lagocephalus sceleratus</i> (Gmelin, 1789) Along the Egyptian Coast, Eastern Mediterranean Sea

Abstract: Stock of pufferfish Lagocephalus sceleratus was evaluated using specimens that collected monthly from the commercial fishing boats at landing sites along whole the Egyptian Mediterranean coast during 2012. Specimens were ranged from 5 to 83cm (TL) in length with an average 43.01± 13.5cm and total weight from 2.1-5400g with an average of 1103.27±850.83 g. The length-weight relationship revealed negative allometric growth for males, females and combined sexes with insignificant difference between males and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Despite the multiple negative impacts of L. sceleratus, most Mediterranean studies have been dedicated to the high content of tetrodotoxin (TTX) in its tissues, with only a handful investigating its biology (Sabrah 2006;Aydin 2011;Nader et al 2012;Kalogirou 2013;Farrag 2014;Khalaf et al 2014;Rousou et al 2014;Ersönmez et al 2017;Zengin and Türker 2020). As well, two studies reported on the abundance of L. sceleratus in Egypt (Farrag et al 2015;Elhaweet et al 2016) and another from Antalya Bay, Turkey (Özbek et al 2017).…”
Section: Impacts On Fishers and Other Personsmentioning
confidence: 99%
“…Despite the multiple negative impacts of L. sceleratus, most Mediterranean studies have been dedicated to the high content of tetrodotoxin (TTX) in its tissues, with only a handful investigating its biology (Sabrah 2006;Aydin 2011;Nader et al 2012;Kalogirou 2013;Farrag 2014;Khalaf et al 2014;Rousou et al 2014;Ersönmez et al 2017;Zengin and Türker 2020). As well, two studies reported on the abundance of L. sceleratus in Egypt (Farrag et al 2015;Elhaweet et al 2016) and another from Antalya Bay, Turkey (Özbek et al 2017).…”
Section: Impacts On Fishers and Other Personsmentioning
confidence: 99%
“…This species was first recorded in the Mediterranean in 2003, from Gokova Bay in southwestern Turkish waters (Akyol et al 2005). It is both the largest (maximum weight of 10 kg; Ulman et al 2022) and most abundant pufferfish species in many localities in the eastern Mediterranean (Farrag et al 2015, Turan 2022. Within just ten years of its first Mediterranean record, it expanded rapidly to nearly every Mediterranean sub-region (strangely, with the exception of southern France and Corsica), and within 15 years it was also recorded in the much cooler Black Sea and the Strait of Gibraltar (Rambla- Alegre et al 2017, Bilecenoglu andOzturk 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Goher et al, 2021). The freshwater pufferfish Tetraodon lineatus is considered a discarded catch in Lake Nasser as pufferfishes, in general, are prohibited by the Egyptian law neither for fishing nor trading due to their toxicity as food (Farrag et al, 2022). Consequently, the population of the pufferfish has increased recently causing losses to entangled fish and damage to the fishing gears (Farrag et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tetraodontidae species range in size from about 7cm to over 75cm. They have four large teeth that are fused into an upper and lower plate; this gives them their name ("tetra" meaning four and "odont" meaning teeth), and the body is typically spiny with short fins (Farrag, 2022). Most tetraodontids feed on molluscs such as clams or oysters; some also feed on crustaceans or small fish.…”
Section: Introductionmentioning
confidence: 99%